Testing unified growth theory: Technological progress and the child quantity-quality tradeoff - Jakob Brøchner Madsen; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
A core mechanism of unified growth theory is that accelerating technologicalprogress induces mass education and, in interaction with child quantity-quality substitution, a decline in fertility. Using unique new data for 21 OECD countries over theperiod 1750-2000, we test, for the first time, the validity of this core mechanism of unified growth theory. We measure a country's technological progress as patents per capita, genetic-distance weighted foreign patents, and investment in machinery, equipment and intellectual property products. Controlling for other confounders like income, mortality, thegender wage gap, indicators for child labor, compulsory schooling, and time- and country-fixed effects, we establish a strong positive impact of technological progress on investmentsin education and a strongly negative one on fertility. Using two-stage regressions, we assess the child quantity-quality substitution that can be motivated by technological change. We estimate that a 10 percent increase of enrollment in primary and secondary school isassociated with a decline of the general fertility rate by 3 to 4 percent.
Keywords: O40; O30; N30; J10; I25; 330; technological progress; fertility; education; quantity-quality trade-off; unifiedgrowth theory